Optimizing the water-ecosystem-food nexus using nature-based solutions at the basin scale - Maragkaki, Antonia; Koukianaki, Evangelia A.; Lilli, Maria A.; Efstathiou, Dionissis; Nikolaidis, Nikolaos P. (Frontiers in Water, 2024)
The Water Ecosystem Food (WEF) Nexus duly acknowledges the complex interdependencies among water, ecosystems, and food production, underscoring Nature Based Solutions (NBS) as an efficacious strategy for navigating these interconnections. In this research, four different NBS (terraces, riparian forest, livestock management and agro ecological practices) were assessed in terms of their impact to WEF Nexus. The Karst-SWAT and the one-dimensional Integrated Critical Zone (1D-ICZ) models were used to simulate the impact of NBS on water quantity and quality as well as on soil ecosystem services of Koiliaris River Basin, which serves as an illustrative example of a basin that has experienced severe soil and biodiversity degradation. The Karst-SWAT model showed that a combination of NBS of terraces and riparian forest can reduce soil erosion and the sediment load by 97%. The 1D-ICZ model successfully simulated the soil-plant-water system and showed that agro ecological practices affect biomass production, carbon and nutrient sequestration, soil structure and geochemistry.